Perancangan Sistem Kendali Suhu Pada Mesin Pengering Hybrid Menggunakan Metode Fuzzy Logic: Design of Temperature Control System on Hybrid Drying Machine using Fuzzy Logic Method - Dhimas Satria; Erny Listijorini; Muhammad Ramdhan Nurghodan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2015)
Food security is condition related to food supply sufficient in quantity and quality, safety, diversity, nutritious content, equitability and affordability. Post harvest handling of paddy is a very strategic effort in order to support the increase of rice production and food security. Drying is an activity on post harvest that aimed to reduce water content. Various type of paddy’s drying machine has been constructed to enhance drying process. However, most drying machine constructed in large dimension and operated using fossil fuel. To overcome these problems, hybrid technology is proposed, i.e. grain-drying machine using combination of solar and biomass energy. This machine is equipped with fuzzy logic control system using microcontroller Arduino Mega 2560 R3 as fan velocity control center based on reading of sensor HT11 that able to detect temperature and humidity in drying room also sensor K Type thermocouple Max6675 that detect temperature in combustion chamber and heat exchanger. This research aimed to support continuity of drying process in order to determine each sensor’s period to achieve their setting point. Based on 90 minutes trial period, the result show maximum temperature reduction 2,17% (wet basis), maximum temperature 50ºC, setting point for temperature (45ºC) achieved in 60 minutes, minimum humidity 18%, and setting point for humidity achieved in 30 minutes.